Intra- and inter-species interactions within biofilms of important foodborne bacterial pathogens - Giaouris, Efstathios; Heir, Even; Desvaux, Mickaël; Hébraud, Michel; Møretrø, Trond; Langsrud, Solveig; Doulgeraki, Agapi; Nychas, George-John; Kačániová, Miroslava; Czaczyk, Katarzyna; Ölmez, Hülya; Simões, Manuel (Frontiers in Microbiology, 2015)
A community-based sessile life style is the normal mode of growth and survival for many bacterial species. Under such conditions, cell-to-cell interactions are inevitable and ultimately lead to the establishment of dense, complex and highly structured biofilm populations encapsulated in a self-produced extracellular matrix and capable of coordinated and collective behavior. Remarkably, in food processing environments, a variety of different bacteria may attach to surfaces, survive, grow and form biofilms. Salmonella enterica, Listeria monocytogenes, Escherichia coli and Staphylococcus aureus are important bacterial pathogens commonly implicated in outbreaks of foodborne diseases, while all are known to be able to create biofilms on both abiotic and biotic surfaces. Particularly challenging is the attempt to understand the complexity of inter-bacterial interactions that can be encountered in such unwanted consortia, such as competitive and cooperative ones, together with their impact on the final outcome of these communities (e.g. maturation, physiology, antimicrobial resistance, virulence, dispersal). In this review, up-to-date data on both the intra- and inter-species interactions encountered in biofilms of these pathogens are presented. A better understanding of these interactions, both at molecular and biophysical levels, could lead to novel intervention strategies for controlling pathogenic biofilm formation in food processing environments and thus improve food safety.